A "cold path" for Gulf Stream - troposphere connection - Czaja,A; Vanniere,B; Dacre,H (Journal of Climate, 2017)
The mechanism by which the Gulf Stream sea surface temperature (SST)front anchors a band of precipitation on its warm edge is still a matter of debateand little is known about how synoptic activity contributes to the meanstate. In the present study, the influence of the SST front on precipitationis investigated during the course of a single extratropical cyclone using a regionalconfiguration of the Met Office Unified Model. The comparison of acontrol run with a simulation in which SST gradients were smoothed broughtthe following conclusions: a band of precipitation is reproduced for a singleextratropical cyclone and the response to the SST gradient is dominated bya change of convective precipitation in the cold sector of the storm. Severalclimatological features described by previous studies, such as surface windconvergence on the warm edge or a meridional circulation cell across the SSTfront, are also reproduced at synoptic time scales in the cold sector. Based onthese results, a simple boundary layer model is proposed to explain the convectiveand dynamical response to the SST gradient in the cold sector. In thismodel, cold and dry air parcels acquire more buoyancy over a sharp SST gradientand become more convectively unstable. The convection sets a pressureanomaly over the entire depth of the boundary layer which drives wind convergence.This case study offers a new pathway by which the SST gradientcan anchor a climatological band of precipitation.